(untitled) (Journal of actual problems of jurisprudence, 2018)
This article discusses the existing criminal procedure science approaches to the definition of the concept of «proof» and its relation to the category of «knowledge.» The study is based on current scientific achievements, which are subject to critical evaluation, with the aim of gaining new scientific results. The study used the formal-logical method of interpretation of the rules of criminal procedure. The subject of study is considered in the development of using the principle of the unity of analysis and synthesis. These results contribute to the improvement of the law of criminal procedure and evidence of the mechanism of the process with the use of undercover investigations. Key words: criminal procedure, evidence, knowledge; unspoken investigations; operatively-search activity.